1977
DOI: 10.1152/ajpheart.1977.232.1.h49
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atrial pacing on regional myocardial gas tensions with critical coronary stenosis

Abstract: Changes in myocardial carbon dioxide (PmCO2) and oxygen tension (PmO2) measured by mass spectrometry have been shown to reflect quantitatively progressive degrees of regional myocardial ischemia associated with stepwise reduction in coronary blood flow. The present study utilized mass spectrometry to assess the severity of regional myocardial ischemia developing during atrial pacing in the presence of a flow-limiting proximal critical coronary artend subendocardial layers was measured by the radioactive micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The present study employs a previously wellcharacterized, anesthetized, open-chest canine model to study the mechanism of nitroglycerin's beneficial effect on regional myocardial ischemia, induced distal to a fixed, flow-limiting coronary stenosis by atrial pacing (O'Riordan et al, 1977). This preparation is designed to model a milder degree of reversible ischemia, such as would be present during angina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study employs a previously wellcharacterized, anesthetized, open-chest canine model to study the mechanism of nitroglycerin's beneficial effect on regional myocardial ischemia, induced distal to a fixed, flow-limiting coronary stenosis by atrial pacing (O'Riordan et al, 1977). This preparation is designed to model a milder degree of reversible ischemia, such as would be present during angina.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent clinical studies have demonstrated that nitroglycerin can be administered safely to patients with acute myocardial infarction by intravenous infusion with consistently beneficial effects on indices of myocardial ischemia (Borer et al, 1975, Come et al, 1975, Flaherty et al, 1976. The ability of nitroglycerin to relieve ischemia in either clinical situation may result from dilating effects on either peripheral arteries or veins, or both, which might decrease determinants of myocardial oxygen demand, or from direct effects on the coronary circulation which might increase myocardial oxygen suppiy-The present study employs a previously wellcharacterized, anesthetized, open-chest canine model to study the mechanism of nitroglycerin's beneficial effect on regional myocardial ischemia, induced distal to a fixed, flow-limiting coronary stenosis by atrial pacing (O'Riordan et al, 1977). This preparation is designed to model a milder degree of reversible ischemia, such as would be present during angina.…”
mentioning
confidence: 99%
“…Conversely, at a given resting heart rate, blood flow through a coronary artery remains constant even up to about 85% stenosis (31) because the predominant resistance to flow resides in the arterioles of the coronary microcirculation. When pacing at increased heart rates in the presence of a major coronary stenosis, evidence indicates potentially substantial reduction in flow through the stenosed coronary artery (32), even though the level of global ventricular myocardial blood flow may not change (3) or even increase. The reason for the pairing effects appear similar to those dis cussed in a recent study in which a potent coronary vasodilator (dipyridamole) was administered in open chest dogs with extracoronary partial occluders (4).…”
Section: Discussionmentioning
confidence: 99%
“…Since the original description of the direct measurement of Pmcoj (Brantigan et al, 1972a), subsequent studies have confirmed the increase of Pmco? during myocardial ischemia or anoxia (Brantigan et al, 1972b;Furuse et al, 1973;Khuri et al, 1975aKhuri et al, , 1975bMacGregor et al, 1974;O'Riordan et al, 1977aO'Riordan et al, , 1977b. Even with lesser degrees of ischemia, it was observed (O'Riordan et aL, 1977b) that Pmcc>2 provides a much more sensitive index of ischemia than myocardial Pch measurements, since Pmcc^ changes more extensively; the magnitude of PmccHi rise also was related to the degree of S-T segment change (O'Riordan et al, 1977a, Khuri et al, 1975c.…”
Section: Discussionmentioning
confidence: 99%